Development of MEMS cantilever-based biosensor - Ab Rahim, Rosminazuin; Za'bah, Nor Farahidah (2015)
The research developments in biosensor are progressing tremendously, not only contributed by arising security and medical concern in the society but also rapid advancements in Micro Electro Mechanical System (MEMS) technology. Among the developed micron-sized biosensor devices in MEMS technology, microcantilever-based biosensors are identified as the most promising candidates for its high sensitivity, high resolution and label-free molecular recognition. Integrated with on-chip piezoresistive readout scheme, the microcantilever biosensor provides promising developments in the integration of MEMS portable analytical device. However, the realization of the piezoresistive microcantilever biosensor through various microfabrication techniques is not straightforward. Microcantilever sensor typically comes in a rectangular shape which usually comprises of two layers of piezoresistor and microcantilever. This design has its fabrication issue such as an interfacing problem between the piezoresistive and microcantilever layers and complex fabrication process. Therefore, this work attempts to provide the process development of effective design of piezoresistive microcantilever (PRM) biosensor through simple and reliable fabrication processes using bulk micromachining technique. In this work, a novel paddle-like microcantilever structure with 50 µm x 50 µm square hole located at the clamped edge is proposed. The incorporated square hole acts as a stress concentration region by maximizing the Mises stress value. The design consideration is analyzed and verified using a finite element solver, CoventorWare 2008. At a dimension of 450 µm x 150 µm x 2 µm, a mechanical displacement of 5 µm for 1 µN applied load results in sensitivity of ΔR/R of 4.84 x 10-3. The development of single-layer doped silicon piezoresistive microcantilever with dual-leg rectangular microcantilever does not only simplify the fabrication process due to reduced fabrication steps, but also conveniently eliminates the interfacing problem that commonly exists in multilayer structures. Connecting to on-chip Wheatstone bridge circuitry, the dual-leg design of the device also ensures efficient current distribution in the piezoresistive microcantilever sensor at relatively higher sensitivity compares to typical rectangular-shaped microcantilever.